PENERAPAN SISTEM PAKAR UNTUK DIAGNOSA GANGGUAN AUSTISM PADA ANAK MENGGUNAKAN METODE FUZZY MAMDANI - Hasanul Fahmi (Lembaga Penelitian dan Pengabdian (LPPM) STMIK Pelita Nusantara Medan, 2018)
Autism Spectrum Disorder (autism) is a disorder that begins and is experienced in childhood, which makes it unable to form normal social or communication relationships, as a result the child is isolated from other humans. Disrupted development especially in communication, social interaction and behavior. But the problem that arises is how to find out whether a child has autism or not, as well as how to manage it optimally. One of them is the expert system application to diagnose Autism Spectrum Disorder (ASD) with fuzzy logic. Fuzzy logic is an appropriate way to map an input space into an output space. This application was created as a tool to diagnose autism based on physical symptoms suffered by patients, using the mamdani method. System input is a symptom of autism, while the system output is a Normal Child (not autistic) and an Autistic Child. The process of calculating the system is carried out with 4 stages of mamdani namely: Formation of fuzzy sets, Implications of rules, Composition of rules and Defuzzyfication.